Tumour–brain crosstalk restrains cancer immunity via a sensory–sympathetic axis - Haohan K. Wei; Chuyue D. Yu; Bo Hu; Xing Zeng; Hiroshi Ichise; Liang Li; Yu Wang; Ruiqi L. Wang; Ronald N. Germain; Rui B. Chang; Chengcheng Jin (Nature, 2026)
Abstract Body–brain communication has emerged as a key regulator of tissue homeostasis 1–5 . Solid tumours are innervated by different branches of the peripheral nervous system and increased tumour innervation is associated with poor cancer outcomes 6–8 . However, it remains unclear how the brain senses and responds to tumours in peripheral organs, and how tumour–brain communication influences cancer immunity. Here we identify a tumour–brain axis that promotes oncogenesis by establishing an immune-suppressive tumour microenvironment. Combining genetically engineered mouse models with neural tracing, tissue imaging and single-cell transcriptomics, we demonstrate that lung adenocarcinoma induces innervation and functional engagement of vagal sensory neurons, a major interoceptive system connecting visceral organs to the brain. Mechanistically, Npy2r -expressing vagal sensory nerves transmit signals from lung tumours to brainstem nuclei, driving elevated sympathetic efferent activity in the tumour microenvironment. This, in turn, suppresses anti-tumour immunity via β 2 adrenergic signalling in alveolar macrophages. Disruption of this sensory-to-sympathetic pathway through genetic, pharmacological or chemogenetic approaches significantly inhibited lung tumour growth by enhancing immune responses against cancer. Collectively, these results reveal a bidirectional tumour–brain communication involving vagal sensory input and sympathetic output that cooperatively regulate anti-cancer immunity; targeting this tumour–brain circuit may provide new treatments for visceral organ cancers.